Patentability of Chemical Selection Inventions: The Olanzapine and Escitalopram Decisions - Ahn, Hyewon (Munich Intellectual Property Law Center - MIPLC, 2011)
The thesis is a response to the recent decisions of the German Federal Court of Justice on the patentability requirements of selection inventions, namely, the Olanzapine and Escitalopram decisions.